The Shaping of Cancer by the Tumour Microenvironment and Its Relevance for Cancer Therapy - Madureira, Patrícia Alexandra Saraiva (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
In this book, we present a compilation of original research articles as well as review articles that are focused on improving our understanding of the molecular and cellular mechanisms by which cancer cells adapt to their microenvironment. These include the interplay between cancer cells and the surrounding microenvironmental cells (e.g., macrophages, tumor-infiltrating lymphocytes and myeloid cells) and microenvironmental environments (e.g., oxidative stress, pH, hypoxia) and the implications of this dynamic interaction to tumor radioresistance, chemoresistance, invasion and metastasis. Finally, the importance and relevance of these findings are translated to cancer therapy.